Innate Immune Cell Suppression and the Link With Secondary Lung Bacterial Pneumonia - Morgan, David J.; Casulli, Joshua; Chew, Christine; Connolly, Emma; Lui, Sylvia; Brand, Oliver J.; Rahman, Rizwana; Jagger, Christopher; Hussell, Tracy (Frontiers in Immunology, 2018)
Secondary infections arise as a consequence of previous or concurrent conditions and occur in the community or in the hospital setting. The events allowing secondary infections to gain a foothold have been studied for many years and include poor nutrition, anxiety, mental health issues, underlying chronic diseases, resolution of acute inflammation, primary immune deficiencies, and immune suppression by infection or medication. Children, the elderly and the ill are particularly susceptible. This review is concerned with secondary bacterial infections of the lung that occur following viral infection. Using influenza virus infection as an example, with comparisons to rhinovirus and respiratory syncytial virus infection, we will update and review defective bacterial innate immunity and also highlight areas for potential new investigation. It is currently estimated that one in 16 National Health Service (NHS) hospital patients develop an infection, the most common being pneumonia, lower respiratory tract infections, urinary tract infections and infection of surgical sites. The continued drive to understand the mechanisms of why secondary infections arise is therefore of key importance.